Graphene-based materials for bone tissue engineering - Oktay, Busra; Ozerol, Esma Ahlatcioglu; Ustundag, Cem Bulent (YILDIZ TECHNICAL UNIV, 2024)
Bone is capable of regenerating itself when it suffers minor injuries. However, treatment of bone that does not regenerate due to major injuries usually requires a surgical application. On the other hand, tissue engineering aims to eliminate problems such as lack of donor tissue and incompatibility that occur in these surgical interventions. Scaffolds are the most important structure produced to fulfill this goal of tissue engineering. Scaffolds provide an environment for cell attachment, proliferation, and differentiation, thereby helping to form new tissue. Some properties such as mechanical properties, surface properties, biodegradability, biocompatibility, and porosity should be considered during the designing of the scaffold. The creation of the scaffold for the determined tissue is related to both the materials used and the production methods. The use of graphene and its derivatives in scaffolds are one of the important applications in tissue engineering as a regulator for cell proliferation and differentiation. Graphene (Gr) and its derivatives have a significant role in bone regeneration thanks to their mechanical and biological properties when used in bone tissue engineering applications. This study reports the importance and advantages of using graphene-based biomaterials in scaffolds for bone tissue engineering. The biological properties of graphene-based biomaterials obtained in various studies have improved and there has been an increase in the adhesion and proliferation of osteoblasts.
Keywords: Graphene; Tissue engineering; Stem Cell; Scaffold; Bone; MECHANICAL-PROPERTIES; IN-VITRO; STEM-CELLS; ANTIBACTERIAL ACTIVITY; GENE DELIVERY; NANO-GRAPHENE; OXIDE; SCAFFOLDS; NANOMATERIALS; COMPOSITES; Engineering